Letters to a new developer : what I wish I had known when starting my development career - Moore, Dan (Apress L.P., 2020)
Learn what you need to succeed as a developer beyond the code. The lessons in this book will supercharge your career by sharing lessons and mistakes from real developers. Wouldnt it be nice to learn from others career mistakes? "Soft" skills are crucial to success, but are haphazardly picked up on the job or, worse, never learned. Understanding these competencies and how to improve them will make you a more effective team member and a more attractive hire. This book will teach you the key skills you need, including how to ask questions, how and when to use common tools, and how to interact with other team members. Each will be presented in context and from multiple perspectives so youll be able to integrate them and apply them to your own career quickly. You will: Know when the best code is no code Understand what to do in the first month of your job See the surprising number of developers who cant program Avoid the pitfalls of working alone.